APLIKASI PLTS ON GRID PADA USAHA PEMBESARAN LELE - Fahru Nurosyid; Agus Supriyanto; Risa Suryana; Yofentina Iriani (Universitas Sebelas Maret, 2018)
Application of on-grid PLTS on the effort of catfish enlargement aims to reduce the cost for the fulfillment of electrical energy, increase knowledge and train the skills to assemble PLTS on grid. Farmers catfish use electrical energy to power the water pump. PLTS on grid enables saving on electricity costs. The use of on-grid PLTS does not require an electric storage battery. The overproduction of electricity from PLTS allows it to be sold to PLN. If there is a shortage of electricity, then electricity is purchased from PLN. Public knowledge about PLTS can be introduced in theory and practice of PLTS installation scale 2000 WP (watt peak). The use of 2000 WP can produce 9.2 KWH / day in sunny conditions.e